2019
DOI: 10.1016/s1474-4422(19)30069-9
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine mesylate in patients with intracerebral haemorrhage (i-DEF): a multicentre, randomised, placebo-controlled, double-blind phase 2 trial

Abstract: ContributionsMagdy Selim --organized the trial hypotheses, designed the trial, provided guidance about the data analysis and interpretation and presentation of the data, and drafted most of the sections of the manuscript. Lydia Foster --involved in the statistical analysis and data interpretation, and Contributed to the development and revisions to the manuscript. Claudia Moy --involved in the oversight of the trial conduct and progress Guohua Xi --organized the trial hypotheses, and provided critical revision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
141
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(147 citation statements)
references
References 32 publications
1
141
0
Order By: Relevance
“…ICH exhibits high disability and mortality rates. Moreover, ICH has become a heavy burden for global health care systems and societies (Selim et al, 2019). Supportive medical care has represented the main treatment for ICH but has yielded an insufficient efficacy (Hanley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…ICH exhibits high disability and mortality rates. Moreover, ICH has become a heavy burden for global health care systems and societies (Selim et al, 2019). Supportive medical care has represented the main treatment for ICH but has yielded an insufficient efficacy (Hanley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Deferoxamine has currently reached clinical trials for ICH. The Deferoxamine Mesylate in Patients with Intracerebral Haemorrhage (i‐DEF) phase 2 trial evaluated clinical outcomes after deferoxamine treatment and showed promising results after 180 days (mRS 0‐2 of 45.2% in the deferoxamine group vs 35.6% in the placebo group), although the trial did not meet the primary outcomes at 90 days. Clinical outcome differences in favor of deferoxamine exceeded the prespecified futility threshold at 180 days which was not met at 90 days, showing future need to explore deferoxamine.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the two trials were somewhat contradicting and hence, no clear answer could be derived from them. A phase II trial failed to prove that the iron chelator deferoxamine, used as a neuroprotective agent, improved outcomes in ICH [3]. Tranexamic acid, an antifibrinolytic drug, was investigated in a large randomized placebo-controlled trial [4].…”
Section: Reza Behrouzmentioning
confidence: 99%